Broń strzelcza piechoty zaciężnej w latach 1471-1500 - Grabarczyk, Tadeusz (Acta Universitatis Lodziensis. Folia Historica, 2000)
Registers of the mercenary infantry give many information about types of weapon and its quality. In Warsaw archive we have rolls from 1471, 1477 and 1496-1500 with information about 7000 mercenaries. In rolls we meet different descriptions of quality of crossbows like: good, bed, new, old, used, repaired. We can clasify about 47% of crossbows as bed, basing on the sources from 1471 and 1477, which contain all these terms. In 1496 we have 14%, and in 1498 – 22% bad or old crossbows. Registers give also information about different types of crossbows used by soldiers. They had crossbows with two kinds of bow - horn or steel. Only two from 597 mercenaries had this last type in 1496, similary in 1498, 9 from 725 crossbowmen possesed steel bows. Soldiers used three types of bend mechanism. The oldest one hed the bow-string stretched by hook fastened to soldier’s belt. This type is named kryg in Polish sources. Second kind of belt mechanism is goat’s foot called hewar in medieval Poland (from word „lewar” – lever). Drawing mechanism, which we know as cranequin or windelass appeared in sources as klyky (from Czech word klika – crank) and this is the third kind of mechanism. All these three different kinds of drawing mechanism could be used by soldiers of the one troop at the same time. Second typ of shooting weapon was bow. This kind of arms was unpopular among mercenaries in end of XV C. Only two soldiers used bows. First bow we meet in 1498 (it is 1 from 725 shooters). Second men with bow appeared in 1500 (rolls from this year mention 1 bowmen among 72 crossbowmen).